Implementation of Educational Supervision by School Principals: Analysis of Impact on Catholic Religious Education Teacher Performance and Educational Quality in Elementary Schools - Maria Koriyanti Nona Yevi; Yoseph Belen Keban; Alfonsus Mudi Aran (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Educational supervision serves as a key instrument in improving educational quality; however, its implementation in elementary schools often faces systemic challenges that affect teacher performance and learning quality. This study aims to analyze the implementation of educational supervision by school principals to improve the performance of Catholic Religious Education (CRE) teachers in enhancing educational quality at Inpres Natarita Elementary School. The research employs a descriptive qualitative approach with the school principal and CRE teacher as research subjects. Data collection was conducted through in-depth interviews, participatory observation, and documentation. Data analysis used the interactive model of Miles and Huberman with stages of data reduction, data presentation, and conclusion drawing.The findings reveal significant disparities between the implementation of administrative supervision and academic supervision. Administrative supervision is consistently implemented but remains procedural-mechanistic in nature, while academic supervision experiences systematic deficits with minimal frequency (once per semester). This condition impacts the competence-performance gap phenomenon in CRE teacher performance, characterized by the dominance of lecture methods, limited learning innovation, and minimal professional initiative. Educational quality shows acceptable achievement in graduation rates but has not been optimal in potential realization and educational value-added.Educational supervision at SDI Natarita has not achieved optimal effectiveness due to a paradigm that remains compliance-oriented rather than development-oriented. A fundamental reorientation toward holistic and transformative supervision is needed to optimize teacher performance and educational quality.